Kesulitan Siswa Kelas XII MIA SMA Negeri Di Kota Palangka Raya Tahun Ajaran 2018/2019 Dalam Memahami Konsep Sel Elektrolisis Yang Ditelusuri Menggunakan Instrumen Two Tier Multiple Choiche - Anastasia Dimas Febyanti; Suandi Sidauruk; Abdul Hadjranul Fatah (Jurnal Ilmiah Kanderang Tingang, 2020)
Electrolysis cell is the study of the process of changing electrical energy into chemical energy. Electrolysis cell in particular are closely related to daily life so that it becomes one of the important things in chemistry, but this concept itself has a fairly high level of abstractness. This abstract is one of the reasons students have difficulty understanding chemical concepts. This study aims to describe the difficulties of class XII MIA high school students in the city of Palangka Raya in the academic year 2018/2019 in understanding the concept of electrolysis cells that are traced using two tier multiple choice instruments. The subjects of this study were 265 students of MIA class XII. This research was conducted in the even semester of the 2018/2019 school year. Student difficulty data were netted using the Electrolysis Cell Concept Understanding Test and conducted interviews with students who were experiencing difficulties. The data that has been obtained is then analyzed descriptively. The results showed that the percentage of students who had difficulty understanding the concept of electrolysis was 68.39%.